EUPHEMISMS IN MODERN ENGLISH: LINGUISTIC AND SOCIAL FUNCTIONS (Ustozlar uchun, 2026)
Euphemism is a common language feature that shows the connection between language, culture, and social norms. In modern English, euphemisms are often used to soften expressions about death, illness, politics, social inequality, and other sensitive issues. This article looks at euphemisms from linguistic and sociolinguistic angles, focusing on how they are formed and their social roles. Drawing on insights from Keith Allan and Kate Burridge, the study investigates how euphemisms act as politeness strategies, ways to save face, and methods of social manipulation. The analysis shows that euphemisms are not just replacements for words. They reflect cultural values, power dynamics, and communication goals. The findings highlight that euphemistic language significantly influences perceptions and helps maintain social harmony in today's English-speaking societies.